Pengaruh Pengetahuan, Sikap dan Keterampilan Perawat Terhadap Kepuasan Pasien - Meilina, Meilina; Bernarto, Innocentius (JURNAL ADMINISTRASI BISNIS (JAB), 2021)
This study aims to analyze the positive influence of nurses' knowledge, attitude and skills on patient satisfaction who receive wound care at the Wocare clinic. The sampling technique in this study was convenience sampling. The large number of samples used was 132 respondents. Data collection techniques using a questionnaire. Data analysis used the partial least square-structural equation modeling (PLS-SEM) approach by utlilizing SmartPls program. The results showed that knowledge, attitude, and skills have a positive effect on patient satisfaction.